Implementasi Software CSI ETABS dan CSI Detail Pada Gedung 15 Lantai Di Desa Ngeling Terhadap Peraturan SNI 2847 tahun 2019 - Istiqomah, Nurul; Rochmanto, Decky; Umam, Khotibul (Jurnal Civil Engineering Study, 2024)
A hospital is a health service institution that provides comprehensive individual health services that provide inpatient, outpatient and emergency services. The development of the human population will continue to increase from year to year. With this population growth, vertical development can help with this problem. In the era of digital globalization, there are many advanced technologies that can make things easier for people in various fields, including Civil Engineering. Based on this, the author carried out hospital construction planning using CSI ETABS and CSI Detail software analysis. In planning the hospital construction, it is planned to be 15 floors high using the SNI 2847 – 2019 reference with a concrete quality (fc') of 30 MPa. Based on this, the following planning results were obtained: roof plate with a thickness of 10 cm with reinforcement in the x direction Æ10-150 and reinforcement in the y direction Æ10-125; floor plate with a thickness of 10 cm with reinforcement in the x direction Æ10-150 and reinforcement in the y direction Æ10-125 (2) main beam I 350 x 700 lt. 1 main support reinforcement 6D13 and support stirrup reinforcement Æ10-125, field main reinforcement 6D13 and support stirrup reinforcement Æ10-325; main beam I 350 x 700 lt. 2-15 main support reinforcement 8D19 and support stirrup reinforcement Æ10-125, field main reinforcement 8D19 and support stirrup reinforcement Æ10-325; main beam I 350 x 700 lt. 16 main support reinforcement 7D19 and support stirrup reinforcement Æ10-125, field main reinforcement 7D19 and support stirrup reinforcement Æ10-325; main beam II 200 x 400 main support reinforcement 6D13 and support stirrup reinforcement Æ10-75, field main reinforcement 6D13 and support stirrup reinforcement Æ10-175; joist 150 x 300 main support reinforcement 5D19 and support stirrup reinforcement Æ10-100, field main reinforcement 4D19 and support stirrup reinforcement Æ10-150 (3) floor column. 1-5 120 x 120 with main reinforcement 40D25 and stirrup reinforcement Æ10-150; column floor 6-10 95 x 95 with main reinforcement 24D25 and stirrup reinforcement Æ10-150; lt column. 11-15 with main reinforcement 12D25 and stirrup reinforcement Æ10-150; lift column 30 x 30 with main reinforcement 8D25 and stirrup reinforcement Æ10-150 (3) foundation using 40 cm diameter spunpile, pile cap P5 280cm x 280cm, P7 280cm x 280cm, P9 280cm x 280cm and P12 380cm x 380cm using top reinforcement D13-100, bottom reinforcement and shrinkage reinforcement D22-100.